To clear or not to clear: Unpacking soy farmers' decision-making on deforestation in Brazil's Cerrado - Aragão, Rafaela Barbosa de Andrade; Bastos Lima, Mairon G.; Burns, Georgette Leah; Ross, Helen (Frontiers in Sustainable Food Systems, 2022)
Agriculture-driven deforestation has come to the top of the environmental policy agenda as one of the main sustainability issues of current food systems. A major case is soy production in Brazil, the largest grower and exporter of what has become the world's crop of choice for animal feed protein. Soy expansion has contributed to the continuous erasure of the Brazilian Cerrado, a highly biodiverse savanna with significant underground carbon storage that plays vital hydrological functions but remains mostly unprotected. Much of the remaining Cerrado vegetation is located within private farms and can be cleared legally; therefore, understanding soy farmers' attitudes regarding deforestation is paramount. Hence, this study explores and analyzes Brazilian soy farmers' perspectives, attitudes, and behavior concerning land-use change. We draw from the literature and semi-structured interviews with 24 soy farmers in Tocantins State, part of an agricultural frontier region called Matopiba. Our findings show how soy-farmer behavior follows primarily an economic rationale unconcerned with environmental sustainability. Farmers have moved to the frontier attracted primarily by cheap land prices and mainly occupied degraded pastures. Still, they have cleared vegetation directly for planting soy and show little restraint. Although chiefly interested in increasing yields, Brazil's soy farmers feel entitled to open new areas whenever they have the economic means and motivation. They may also engage in pre-emptive deforestation for fear of more stringent forthcoming regulations. Such attitudes offer a cautionary note to strategies that hope to conserve the Cerrado through voluntary behavioral change, such as adopting “best practices” or focusing on improving production in already-open areas. We argue that greater regulatory stringency and enforcement are much more promising pathways in the context of excessive permissiveness to deforestation in the Cerrado and actors oriented by profit and by what they are allowed to do. Well-enforced public policies that legally restrict their deforestation rights and protect the remaining areas of Cerrado would offer a royal road, but supply-chain actors, too, may need to become stricter about requesting conversion-free soy. We conclude that, without such actions, soy farmers' attitudes promise a continuation of business as usual toward the Cerrado's end.